Carbamazepine Clearance and Seizure Stability during Pregnancy - Johnson, Emily L. (2014)
The aims of this study were to characterize the alterations in total and free carbamazepine (CBZ) and total and free carbamazepine-epoxide (CBZ-EPO) clearances during pregnancy; to calculate the change in free fractions of CBZ and CBZ-EPO during pregnancy; and to determine whether seizure worsening is associated with a low ratio to non-pregnant baseline concentration of total or free CBZ or CBZ-EPO. Women on CBZ were enrolled before conception or during pregnancy in this prospective, observational study. Concomitant medications and seizure frequency were recorded. Serum total and free CBZ and CBZ-EPO were collected at each visit. Changes in clearance of all four compounds and free fractions of CBZ and CBZ-EPO were compared to non-pregnant baseline. During pregnancy, the ratios to baseline concentrations of total and free CBZ and CBZ-EPO were compared for months with and without increased seizure frequency. Total and free CBZ and CBZ-EPO clearances were calculated in 15 pregnancies in 12 women. Clearances did not change for any of these compounds during pregnancy. The free fraction of CBZ increased from 0.23 at baseline to a maximum of 0.32 in the third trimester (p=0.008), In the six women on CBZ monotherapy with adequate seizure diaries and blood sampling, seizure worsening did not correspond to a ratio to baseline concentration of less than 0.65 for total or free CBZ or CBZ-EPO. In conclusion, total and free CBZ and CBZ-epoxide clearances did not change substantially during pregnancy, and seizure frequency worsening was not associated with decreased concentrations of total or free CBZ; therefore, therapeutic drug monitoring may not be necessary for all women on CBZ during pregnancy. Further studies with larger sample sizes are needed before definitive recommendations can be made. CBZ monotherapy may be a relatively safe and cost effective treatment option for women with focal epilepsy syndromes during pregnancy.